BIG DATA: KEAMANAN DAN MANFAAT DALAM BISNIS MODERN - Alfia Utami; Muhammad Irwan Padli Nasution (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This journal explores the challenges of big data security, threat identification, and effective data protection methods. Based on empirical data analysis, the implementation of big data can enhance operational efficiency, marketing strategies, and business decision-making. However, to realize these benefits, companies must adopt advanced security technologies, strict privacy policies, and effective employee training. A well-integrated approach to leveraging the benefits of big data while adhering to strict security policies can support business growth and increase customer trust.